Adverse events and their management of patients with the use of deoxycholic acid for the treatment of submental fat: uma integrative review (Research, Society and Development, 2023)
The objective was to present scientific and clinical evidence of adverse events reported in patients using deoxycholic acid to reduce localized adiposity in the submental region, as well as to identify and report the management of these events. This study was conducted in the format of an integrative literature review that carried out a qualitative analysis of articles published in the last ten years (2013-2022). 116 findings were found by crossing the descriptors and after the identification and screening process, 5 scientific articles were selected to compose this research. When analyzing the selected articles, we can observe the presence of adverse events in most patients with the use of deoxycholic acid, being mainly related to the application procedure and reporting that these were mild to moderate, transient and resolved between treatments. However, there is one study that investigated the usefulness of topical/injectable anesthetics, oral analgesics and antihistamines, mechanical compression and cold therapy to improve patient comfort with respect to pain, swelling/edema and bruising after treatment with this substance. Researches like these need to be more evidenced, as it found that the occurrence of adverse events is related to the induced inflammatory process, but also to the ability to administer the substance, in addition to the deep knowledge of the anatomical region. There are common adverse events, but there are occurrences of serious events such as alopecia, nodules, necrosis and paresis of the mandibular marginal nerve. In view of this, the lack of specific safety and management protocols for treatment with this substance stands out.